Pyro- and electromagnetic effects in ferrite/barium titanate composite - Andrey A. Pan'kov (Modern Electronic Materials, 2016)
New solutions for tensors of effective pyroelectromagnetic properties of piezoactive composites on the basis of boundary value problem solution for electromagnetic elasticity have been obtained. For the solution of the boundary value problem, new solutions for singular components of the second derivative Green functions for displacements, electric and magnetic potentials in homogeneous transversal isotropic piezoelectromagnetic medium with ellipsoidal grain of heterogeneity have been used. Calculation results on the concentration dependences for effective coefficients of pyromagnetic and electromagnetic coherence of ferrite/barium titanate composite with ellipsoidal, spherical and fibrous inclusions for various polydisperse structures and those of a layered structure composite have been presented. Considerable influence of the shape of the inclusions, features of relative positioning and inversion of the properties of phases on the effective coefficients of pyromagnetic and electromagnetic coherence of the composite material have been revealed. The conclusion is drawn on the preferable use of the pyroelectric phase as spherical inclusions, and ferrite as the composite matrix. This allows for more than a fivefold increase in the effective constant of pyromagnetic coherence of the composite material in comparison with its value for the same structure but with inversion of properties of phases for constant volume fractions of the ferrite and pyroelectric phases.